Cementless unicompartmental knee replacement allows early return to normal activity - Panzram, Benjamin; Bertlich, Ines; Reiner, Tobias; Walker, Tilman; Hagmann, Sébastien; Gotterbarm, Tobias (BMC musculoskeletal disorders, 2018)
Physical activity and regular participation in recreational sports gain importance in patients’ lifestyle after knee arthroplasty. Cementless unicompartimental Knee replacement with the Oxford System has been introduced into clinical routine. Currently there is no data reporting on the physical activity, return to sports rate and quality of live after medial cementless Oxford Unicompartimental Knee Replacement (OUKR).